Localization accuracy of robotic radiosurgery in 1-view tracking. (March 2019) - Bresolin, Andrea; Beltramo, Giancarlo; Bianchi, Livia Corinna; Bonfanti, Paolo; Eulisse, Marco; Fovanna, Damiano; Maldera, Arcangela; Martinotti, Anna Stefania; Papa, Sergio; Redaelli, Irene; Rocco, Domenico; Secondi, Gianluca; et al.
Highlights: "Actual and planned target positions were studied preserving reciprocal spatial metric". "Biphasic breath-hold CT scans are not a good model for planning in 1-view mode". "The inter-fractional variability cannot be neglected in 1-view treatments". "The spine-ITV distance variation is a source of localization uncertainty". Abstract: Purpose: When a lung lesion is detected by only one couple of X-ray tube and image detector integrated with CyberKnife®, the fiducial-less tracking is limited to 1-view (34% of lung treatments at Centro Diagnostico Italiano). The aim of the study was mainly to determine the margin needed to take into account the localization uncertainty along the blind view ( out-of-plane direction). Methods: 36 patients treated in 2-view tracking modality (127 fractions in total) were included in the study. The actual tumor positions were determined retrospectively through logfile analysis and were projected onto 2D image planes. In the same plots the planned target positions based on biphasic breath-hold CT scans were represented preserving the metric with respect to the imaging center. The internal margin necessary to cover in out-of-plane direction the 95% of the target position distribution in the 95% of cases was calculated by home-made software in Matlab®. A validation test was preliminarily performed using XLT Phantom (CIRS) both in 2-view and 1-view scenarios. Results: The validation test proved the reliability of the method, in spite of some intrinsic limitations. Margins were estimated equal to 5 and 6 mm for targets in upper and lower lobe respectively. Biphasic breath-hold CT led to underestimate the target movement in the hypothetical out-of-plane direction. The inter-fractional variability of spine-target distance was an important source of uncertainty for 1-view treatments. Conclusion: This graphic comparison method preserving metric could be employed in the clinical workflow of 1-view treatments to get patient-related information for customized margin definition.